Biomolecule and surfactant-assisted hydrothermal synthesis of PbS crystals - Titipun Thongtem (2018)
PbS crystals were hydrothermally synthesized using Pb(NO3)2, l-cysteine, and N-cetyl pyridinium chloride in solutions with different pH values at 140 °C. Flower-like, granular and truncated cubic PbS crystals composing of Pb and S were detected using an X-ray diffractometer (XRD), a scanning electron microscope (SEM), a transmission electron microscope (TEM), a selected area electron diffraction (SAED) technique and an energy dispersive X-ray (EDX) analyzer. In addition, a Raman spectrometer revealed the presence of the first and second overtone modes at 436 and 602 cm-1, respectively. Emission spectra of the products were detected at 412 nm using a photoluminescence (PL) spectrometer. © 2007 Elsevier Ltd and Techna Group S.r.l.